Uji Laboratorium: Esterifikasi dan Sulfonasi pada Surfaktan Berbasis Minyak Jentah - Aliami, Alim; Wahyuni, Viola Sri; Anggraini, Devi; Candraningtyas, Aristawidya; Cambo, Andi Atsiilah Besse; Asraf , Muh (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Used cooking oil is a household waste that has the potential to pollute the environment, but it can still be used as a raw material for value-added surfactants. This study aims to examine the process of utilizing used cooking oil through the esterification and sulfonation stages to produce methyl ester sulfonate (MES) surfactants. The research method was carried out experimentally in the laboratory with the stages of pretreatment of used cooking oil, esterification using methanol and KOH catalyst at a temperature of 65–75 °C, followed by washing and purification of methyl esters, and the sulfonation process using H₂SO₄ and neutralization with NaOH. The results showed that the esterification process produced methyl esters with an increased level of purity despite a decrease in volume due to the washing process. The sulfonation stage successfully converted methyl esters into MES with amphiphilic properties suitable as surfactants. This study shows that used cooking oil has the potential to be used as a raw material for environmentally friendly and economically valuable surfactants.